Development Of Ethnomathematics-Based Mathematics Workbooks To Improve Numeracy Literacy - Rahmi Hayati; Nuraina; Novianti; Intan Azura; Wilda Salsabila (PGMI IAIN Lhokseumawe, 2026)
This study aimed to develop an ethnomathematics-based mathematics worksheet (LKPD) to enhance students’ numeracy literacy skills. The research applied a Research and Development (R&D) approach using the 4D model, consisting of the stages of define, design, develop, and disseminate. The findings from the define stage revealed that students’ numeracy abilities were still relatively low, while the teaching materials used in schools had not incorporated local cultural elements into mathematics learning. During the design stage, the worksheet was created by integrating mathematical concepts with local cultural contexts to provide more meaningful and engaging learning experiences. In the develop stage, the LKPD was evaluated by subject experts, media experts, and educational practitioners. The validation results indicated that the product achieved a highly valid category in terms of content, language, presentation, and visual design. Classroom trials demonstrated that the ethnomathematics-based LKPD improved students’ abilities to interpret numerical information, solve contextual mathematical problems, and relate mathematics to everyday situations. In addition, students showed greater participation, enthusiasm, and motivation during learning activities. Therefore, the developed LKPD can serve as an innovative learning resource to support the improvement of students’ numeracy literacy.